State-owned enterprises management: the challenge of a multilevel approach - Agoff, Sergio Leandro (Universidad Nacional del Litoral, 2021)
The article expands the idea that the public management of companies occurs at different levels, integrating a consideration of territorial issues, understood as a "base scale", not always accurately reflected in previous studies on the matter. The paper assumes that the challenge of the public management of companies is to articulate three levels: first, the global, taking into account the questions of international experiences, development models and the question of regional projection and integration; secondly, the territorial, focusing on the link with public and private actors in the specific areas of their activity; and, finally, the organizational, addressing the question of blending between structure and professionalization that might allow sustainable work at the other two levels. The article mainly appeals to secondary sources and discusses from the references provided by the specialized literature.